Assessing competences - developing competences: procedures and quality standards - Bylinski, Ursula [Verfasser] (My University, 2009)
"Procedures and instruments for the assessment of competences afford a particular opportunity in so-called search and transitional phases such as that from school to work to render personally related areas of potential and resources visible and to make them deployable for development processes. At the same time, they may also play a part in recognising (educational) risks at an early stage and instigating preventative support. A multiplicity of various procedures for the assessment and development of competences have emerged and been deployed within the vocational orientation provision of general schools and school-based and extra-school vocational preperation over the course of recent years. The question arising is which procedures are really suitable for the assessment of competences. The present paper presents various procedures and criteria for their evaluation." (Autorenreferat, BIBB-Doku)
Keywords: L 6.2.1 Standards/Gütekriterien; L 6.3.1 Diagnose- & Messinstrumente; L 8 Diagnostik / Eignung; Kompetenzfeststellung; Verfahren; Standardisierung; Berufseinmündung; Erste Schwelle